Hubungan Tingkat Penghasilan Dengan Tingkat Stres Kepala Keluarga Penduduk Dukuh Klile Desa Karangasem Kecamatan Bulu Kabupaten Sukoharjo - ASFIANA, Norita Wahyuniawati (2015)
Background: Stress is a response to somebody that has excessive workload. They who have high risk of stress is the head of the family. It happens because they are expose to demands to earn for their livings. Purpose :To know the correlation between stress level and income level of the head of the family in Klile Hamlet Karangasem Village Sukoharjo Regency. Method:This research using an observational-analytic one with cross-sectional approach, involved 52 respondents with characteristics of sample are head of the family who live and financially responsible for 2-4 family members. Subjects are taken by simple random sampling technique, and using DASS score and monthly income questionnaire as measurement tools. Data were analyzed using spearman corelation test. Results: From the research found that the r value is -0.779 and p value is p < 0.001 it means statistically very significant. Conclusion: There is a very significant negative correlation between stress level and income level of the head of the family in Klile Hamlet Karangasem Village Sukoharjo with strong correlation strength. The lower income level, the higher a stress level.